The Influence of Consumer Trust and Advertising on Consumer Decisions to Make Purchases at Lazada Marketplace - R. Ela Sulastri (Almana : Jurnal Manajemen dan Bisnis, 2022)
The research entitled the influence of consumer trust and advertising on consumer Decision to make purchases at Lazada marketplace is a study of how the magnitude of the influence of trust and the role of advertising on these decisions. Trust is a very basic thing that must be owned by consumers in making purchases in the marketplace, this is based on an online purchasing system. The purpose of this study was to determine the effect of consumer trust and advertising on consumer decisions to buy in the marketplace. Study this using design study descriptive and verification, with method study character quantitative Testing. descriptive in a study this is with use continuum line analysis and analysis verification with use Analysis path (path analysis). The results of the analysis show that consumer trust in the Lazada marketplace is included in the good category, this is supported by the advertising activities carried out by Lazada which are considered good by the respondents. by Lazada has a greater relationship and influence compared to consumer trust, however, when viewed from the magnitude of the influence simultaneously, the two variables studied have a major influence on consumer decisions to make purchases.